"On-Off" Phenomena Related to High Plasma Levodopa. Issue 5867 (16th June 1973) - Claveria, L. E.; Calne, D. B.; Allen, J. G.
Abstract : The neurological deficit and plasma concentrations of levodopa have been studied in a Parkinsonian patient experiencing "on-off" phenomena. Blind evaluations of transient attacks of dysphonia revealed an association between episodes of neurological deterioration and exceptionally high plasma concentrations of levodopa shortly after ingestion. These results indicate that "on-off" phenomena can be toxic reactions to levodopa rather than deteriorations due to inadequate intake or absorption of the drug. Management of patients subject to such attacks should be aimed at minimizing fluctuations in the serum level of the drug.